Development and characterization of three-dimensional woven fabric for ultra violet protection. Issue 4 (6th August 2018) - Nasreen, Adeela; Umair, Muhammad; Shaker, Khubab; Hamdani, Syed Talha Ali; Nawab, Yasir
Abstract : Purpose: The purpose of this paper is to investigate the effect of materials, three dimensional (3D) structure and number of fabric layers on ultraviolet protection factor (UPF), air permeability and thickness of fabrics. Design/methodology/approach: Total 24 fabrics samples were developed using two 3D structures and two weft materials. In warp direction cotton (CT) yarn and in weft direction polypropylene (PP) and polyester (PET) were used. Air permeability, thickness and UPF testings were performed and relationship among fabric layers, air permeability, thickness and UPF was developed. Findings: UPF and thickness of fabrics increases with number of fabric layers, whereas air permeability decreases with the increase in number of fabric layers. Furthermore, change of multilayer structure from angle interlock to orthogonal interlock having same base weave does not give significant effect on UPF. However, change of material from polyester (PET) to polypropylene (PP) has a dominant effect on UPF. Minimum of three layers of cotton/polyester fabric, without any aid of ultraviolet radiation (UV) resistant coating, are required to achieve good. Cotton/polyester fabrics are more appropriate for outdoor application due to their long-term resistance with sunlight exposure. Originality/value: Long-term exposure to UV is detrimental. So, there is need of proper selection of material and fabric to achieve ultraviolet protection. 3D fabrics have yarns in X, Y as well as in Z directions which provide better ultraviolet protection as compared to two dimensional (2D) fabrics. In literature, mostly work was done on ultraviolet protection of 2D fabrics and surface coating of fabrics. There is limited work found on UPF of 3D woven fabrics.